Association of Colon Cancer Susceptibility With P53 Gene Codon 72 and Pai-1 Gene 4g/5g Polymorphisms - Bayram, Banu; Özkurt, Mete; Badak, Bartu; Erkasap, Nilüfer; Erkasap, Serdar; Yıldız, Bülent; İhtiyar, Enver (Muş Alparslan Üniversitesi, 2017)
We aimed to investigate the relationship between colon cancer and p53 gene codon 72 and PAI-1 gene 4G/5G polymorphism in a Turkish study population. Genomic DNA was extracted from 72 patients with colon cancer and 76 controls. PCR technique was used to amplify extracted DNA with proper primers for each polymorphism. For identifying genotypes PCR products were assessed with UV transilluminator by being exposed to agarose gel electrophoresis. There was no statistical difference between colon cancer patients and controls according to p53 gene codon 72 genotype distribution and allele frequencies (p>0.05). Due to PAI-1 gene 4G/5G genotype distribution 4G4G genotype was frequently higher in colon cancer patients compared to controls  (p<0.05). As a conclusion of our study we may assert that p53 gene codon 72 polymorphism should not be related as a susceptibility factor for colon cancer development in the studied Turkish population while PAI-1 gene 4G/5G polymorphism should be related.

Bu çalışmada Türk popülasyonunda kolon kanseri ile p53 geni kodon 72 ve PAI-1 geni 4G/5G polimorfizmleri arasındaki ilişkinin araştırılması amaçlanmıştır. Genomik DNA 72 kolon kanserli hastadan ve 76 kontrol bireyinden izole edilmiştir. Her bir polimorfizm için uygun primerler kullanılarak izolen edilen DNA PCR tekniği kullanılarak amplifiye edilmiştir. PCR ürünleri genotiplerin belirlenmesi için  agaroz jel elektroforezine tabi tutularak  UV translimünatör ile değerlendirilmiştir. p53 geni kodon 72 genotip dağılımı ve allel frekansları incelendiğinde kolon kanserli hastalar ve kontrol bireyleri arasında istatistiksel olarak bir fark belirlenmemiştir (p>0.05). PAI-1 4G/5G genotip dağılımı ve allel frekansları açısından ise 4G4G genotipi kontrol bireylerine göre kolon kanserli hastalarda daha yüksek bulunmuştur (p>0.05). Elde edilen verilere göre çalışmanın yapıldığı Türk popülasyonunda p53 geni kodon 72 polimorfizminin kolon kanseri gelişiminde bir yatkınlık faktörü olamayacağı, PAI-1 4G/5G polimorfizminin ise olabileceği kanısına varılmıştır.
Kolon Kanserine Yatkınlık ile p53 Geni Kodon 72 ve PAI-1 Geni 4G/5G Polimorfizmleri Arasındaki İlişki
msufbd
Keywords: Colon; Cancer; Gene; Polymorphism; PAI-1; Kolon; Kanser; Polimorfizm; PAI-1; p53